2021
DOI: 10.3892/ije.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effects of obesity on pre‑ vs. post‑menopausal breast cancer: The epigenetic mechanisms (Review)

Abstract: Breast cancer (BC) has surpassed lung cancer as the most commonly diagnosed cancer among women in the US, as well as globally. A number of factors evidently contribute to the risk of developing BC, including age, physical activity, overweight/obesity, alcohol consumption, etc. It is of particular importance to study the role of body fatness and its potential influence on the risk of developing BC, as the number of individuals with obesity has increased with an alarming rate worldwide in recent decades. Epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…When compared to conventional treatment, BMS results in more substantial and durable weight loss while improving inflammatory markers, insulin sensitivity (HOMA-IR) and resolving other underlying disease processes, including metabolic syndrome, T2DM, glycosylated haemoglobin (HbA1c), NASH, aromatase activity, visceral obesity, hypoxia and OSA [ 23 , 31 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. RYGB surgery has been shown to decrease macrophage infiltration and crown-like structures (CLS) in subcutaneous adipose tissue (SAT), indicating improvement in local white adipose tissue (WAT) inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to conventional treatment, BMS results in more substantial and durable weight loss while improving inflammatory markers, insulin sensitivity (HOMA-IR) and resolving other underlying disease processes, including metabolic syndrome, T2DM, glycosylated haemoglobin (HbA1c), NASH, aromatase activity, visceral obesity, hypoxia and OSA [ 23 , 31 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. RYGB surgery has been shown to decrease macrophage infiltration and crown-like structures (CLS) in subcutaneous adipose tissue (SAT), indicating improvement in local white adipose tissue (WAT) inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity results in cross-talks between leptin, ER-α receptor, IGF signalling and the transactivation of EGFR, which is thought to increase the risk of postmenopausal breast cancer. Other studies have suggested obesity decreases the risk of developing premenopausal breast cancer [ 74 , 83 , 110 ]. The influence of the ER status in obesity-related breast cancer was elucidated by Feigelson et al (2020), who found that bariatric surgery significantly reduced the future risk of ER+ postmenopausal breast cancer (HR 0.51, 95% CI, 0.38–0.69, p <0.001) but not ER- postmenopausal breast cancer (HR 0.79, 95% CI, 0.41–1.51, p = 0.47) [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity results in epigenetic alterations such as DNA methylation, which has been correlated with the future development of CRC and breast cancer [ 145 , 146 , 147 , 148 , 149 ]. The other main types of epigenetic changes include histone modifications and non-coding mRNA interference.…”
Section: Epigenetic Pathwaysmentioning
confidence: 99%
“…The other main types of epigenetic changes include histone modifications and non-coding mRNA interference. Histone modifications regulate gene expression through the addition or removal of a chemical group (acetylation, methylation, phosphorylation, ubiquitination) which affects the compaction of chromatin [ 149 ]. As discussed in the section on dysfunctional adipocyte exosomes, microRNAs control gene expression by cleaving mRNA or interfering with the production of proteins by coding RNA [ 145 ].…”
Section: Epigenetic Pathwaysmentioning
confidence: 99%